Changes in plasma enzyme activities in professional racing cyclists - Mena, P.; Maynar, M.; Campillo, J. E. (British Journal of Sports Medicine, 1996)
OBJECTIVE: To reports changes in plasma levels in professional racing cyclists. METHODS: Plasma levels of the intracellular enzymes aspartate aminotransferase, alanine aminotransferase, gamma glutamyl transpeptidase, lactate dehydrogenase, and alkaline phosphatase were measured resting and after exercise in professional cyclists participating in two road races: Vuelta Ciclista a Valencia (800 km, beginning of the cyclist season), and the top rank race Vuelta a Espana (2700 km, at the end of cyclist season). RESULTS: A significant increase in plasma aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase was observed at the end of the race over the corresponding paired start values (P < 0.05). The increase in plasma lactate dehydrogenase after the race was only statistically significant (P < 0.05) in the Vuelta a Espana. The longer the duration of the cycle tour race, the greater were the increases in aspartate aminotransferase and alanine aminotransferase levels. The high levels returned to their start values during the overnight resting period. CONCLUSIONS: The presence of these enzymes in the blood is probably due to mechanically damaged muscle cells leaking their contents into the interstitial fluid.